Attitudes of medical professionals towards patient-centredness: a cross-sectional study in H City, China. Issue 1 (21st January 2022) - Song, Weijian; Hao, Yanhua; Cui, Yu; Zhao, Xiaowen; Liu, Wei; Tao, Siyi; Xue, Yuxin; Liu, Chaojie; Zhang, Qiao; Jiao, Mingli; Xu, Weilan; Sun, Hong; et al.
Abstract : Objectives: Patient-centred communication improves patient experiences and patient care outcomes. This study aimed to assess the preference of medical professionals in China towards patient-centred communication under the context of the deteriorating doctor–patient relationship. Methods: A cross-sectional survey of medical professionals was conducted in January and February 2018 in H City of Heilongjiang province, the northeast of China. The Chinese-Revised Patient-Practitioner Orientation Scale (CR-PPOS) was adopted to measure the individual preference of respondents towards patient-centredness in clinical communication. Multivariate logistic regression models were established to identify the sociodemographic (gender, age, marital status and educational attainment) and work experience (years of working, seniority, satisfaction with income, daily workload and perceived doctor–patient relationship) predictors of the preference towards patient-centredness. Patient and public involvement: Not applicable. Results: A total of 618 valid questionnaires were returned. The CR-PPOS demonstrated acceptable reliability and validity. Overall, a low level of preference towards patient-centredness in clinical communication was found. Relatively higher scores on 'caring for patients' (20.42±4.42) was found compared with those on 'information/responsibility sharing' (15.26±4.21). Younger age, higher educational attainment, lower daily workload and a perception of harmonious doctor–patient relationship were associated with a higher preference towards patient-centredness in clinical communication. Conclusions: A low level of preference towards patient-centredness in clinical communication was found in medical professionals in the northeast of China, which may further jeopardise the efforts to improve doctor–patient relationship.